Effectiveness Of Sariva Churna Capsule And Gel In Treating Pittaja Yonivyapad With Reference To Tricomonas Vaginitis - Khatal, Satish; Gajare, Rahul; Gholap, Seema; Bhati, Kirti; Tambe, Namrata; Ghate, Umesh; Bobade, Rahul (Journal of Neonatal Surgery, 2025)
The study was conducted in 40 clinically diagnosed patients of Pittaja yonivyapad and Trichomonas Vaginitis with an objective of clinical evaluation of the efficacy of sariva churna capsule and sariva gel in the management of Pittaja yonivyapad and Trichomonas. These patients were randomly divided into two groups of 20 patients each. It was also observed that the trial drug has its on not only Pittaja yonivyapad but also on Pittaja yonivyapad arising out of Trichomonas indicating its antimicrobial activity against Trichomonas.